Efficacy of L-dopa in Treatment of Aggression, Frontal Lobe Cognitive Functioning and Task Switching Deficits in Parkinson’s Disease Patients - Gul, Amara; Yousaf, Javed (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To assess efficacy of L-dopa treatment on aggression, frontal lobe and task switching deficits in patients with Parkinson’s disease (PD). Study Design: Prospective comparative study. Place and Duration of Study: Bahawal Victoria Hospital and Civil Hospital Bahawalpur, Pakistan, from Apr 2016 to Oct 2017. Methodology: Seventy-five healthy individuals and seventy-five PD patients participated in the study. This study was completed in two testing sessions. Healthy participants had single testing session whereas patients were tested twice (pre and post L-dopa treatment). Participants completed Frontal Assessment Battery, part B TMT, and Buss-Perry Aggression Questionnaire. Results: PD patients (6.13 ± 0.81) showed deficient frontal lobe functioning F (1,48)=14489.66, p<0.001, ηp2=0.99 than healthy individuals (17.93 ± 0.25). Patients (283.05 ± 6.02) had inferior task switching abilities F (1, 48) = 65397.85, p<0.001, ηp2=0.99 than healthy individuals (78.37 ± 3.43). The level of aggression was higher F (1,48)=2369.24, p<0.001, ηp2=0.94 in patients (131.12 ± 12.57) compared with healthy individuals (43.33 ± 9.26). Post L-dopa treatment testing session showed significant improvement in frontal lobe functioning (6.13 ± 0.81 vs. 13.46 ± 1.45), task switching abilities (216.80 ± 13.74 vs. 283.05 ± 6.02) in patients. In addition, aggression was reduced in patients (106.06 ± 1.07 vs. 131.12 ± 12.57). Conclusion: L-dopa was found beneficial to reduce aggression, frontal lobe cognitive and task switching deficits in patients with PD.